CALCULATION OF SOLID SECTION ELEMENTS UNDER CENTRAL COMPRESSION ACCORDING TODIFFERENT STANDARDS (Academic journal Industrial Machine Building Civil Engineering, 2017)
Analysis of different calculating models of the elements of solid section under central compression according to SNIP II-23-81 * DBN B.2.6-163 and EN 01.01.1993 was presented. The comparison of calculations results for I-type, T-type and tube section elements was made. Differences between various standards are declared. Keywords:solid cross-section, central compression, stability of elements.